FEASIBILITY ANALYSIS OF CAPITAL CHILLIES IN SURALAGA DISTRICT EAST LOMBOK REGENCY - Saiful wathan saiful; Rini Endang Prasetyowati; Muhammad Anwar (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2021)
Cayenne pepper is one of the horticultural commodities that can be relied upon to increase farmers' income and state revenue. At first, cayenne pepper was cultivated to meet household consumption needs, namely as vegetables and cooking spices. In addition, cayenne pepper is also consumed by food industry companies that require raw materials for cayenne pepper, for example chili sauce or just a complement to cooking spices. This research was conducted in Suralaga Subdistrict, East Lombok Regency in 2021, from 15 villages 3 villages were taken using a purposive sampling method including Anjani Village, Tebaban Village, Bagek Payung Village, the number of farmers was determined by Quota Sampling as many as 30 people. Proportional Random Sampling and in this study used descriptive methods while data collection was carried out using survey techniques. The objectives of this study are: (1) To determine the costs and income of cayenne pepper farming in Suralaga District, East Lombok Regency. (2) To determine the feasibility of cayenne pepper farming in Suralaga District, East Lombok Regency. (3) To find out the constraints faced by farmers in cayenne pepper farming in Suralaga District, East Lombok Regency. Based on the results of the research, it can be concluded that: (1) Financially, the production cost of Rawit Chili in Suralaga District, East Lombok Regency is Rp. 12,524,018/LLG and Rp. 25,787,271/Ha. And the production value is Rp.18.691.000/LLG and Rp38.485.244/Ha. (2) Farmer's income obtained is Rp.6.166.982/LLG and Rp.12.697.973 /Ha. From the results of the calculation of the R/C Ratio, a value of Rp. 1.4 is obtained, which is greater than 1. This indicates that the Chili Rawit farming in Suralaga District, East Lombok Regency is feasible.